Global Citizenship Education and English Language Teaching in Iran - Alireza sohrabi; Arshya Keyvanfar; Reza Beh-Afarin (Journal of Modern Research in English Language Studies)
Global citizenship education (GCE) is a pedagogical field that has established itself internationally in the past few years being introduced to all countries including Iran where lots of English language learners, are involved with the English Language learning process and language textbooks, as well as language teachers and policy makers who need to face English as the Lingua Franca (EFL) of the postmodern era. Accordingly, the focus of this study has been to investigate the implementation of the GCE in Iran and how the awareness of GCE goals can relate to English language Proficiency of individuals. To this end, a GCE questionnaire was translated in Persian based on Morais and Ogden’s (2010) and was distributed among 400 PhD candidates of different majors in IAU, who were currently involved in taking IAU English Language Proficiency Test (EPT), to investigate the relationship between the two main variables of this study. Both descriptive and inferential statistics including Analysis of Variance and linear regression were carried out. The results showed that there is a significant relationship between the awareness of GCE goals and English language Proficiency. These findings indicate that English Language learning and the related contents can play a significant role in raising awareness regarding global challenges in the world.